1987
DOI: 10.1128/mcb.7.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the high-affinity purine nucleobase transporter in mutant mouse S49 cells does not require a functional wild-type nucleoside-nucleobase transporter.

Abstract: ) has been inserted into nucleoside transport-deficient S49 cells. Two classes of mutants expressing this nucleobase permease were generated. The first, as exemplified by the AE1HADPAB2 cell line, possessed an augmented capacity to transport low concentrations of the three purine bases, hypoxanthine, guanine, and adenine. The second class of mutants, as typified by the AE1HADPAB5 clone, possessed an augmented capability to translocate low levels of hypoxanthine and guanine, but not adenine. Neither the AE,HADP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…34) However, one study reported the involvement of ENT1 in hypoxanthine transport in a murine T-lymphoma cell line, S49, which was mostly inhibited by 10 nM of NBMPR. 35) 4.2. ENT2/SLC29A2 Human ENT2 (hENT2) was identified as a NBMPR-insensitive nucleoside transporter by Crawford et al 36) and Griffiths et al 37) The amino acid sequence of hENT2 is 46% identical to that of hENT1.…”
Section: Facilitative Transport Systemsmentioning
confidence: 99%
“…34) However, one study reported the involvement of ENT1 in hypoxanthine transport in a murine T-lymphoma cell line, S49, which was mostly inhibited by 10 nM of NBMPR. 35) 4.2. ENT2/SLC29A2 Human ENT2 (hENT2) was identified as a NBMPR-insensitive nucleoside transporter by Crawford et al 36) and Griffiths et al 37) The amino acid sequence of hENT2 is 46% identical to that of hENT1.…”
Section: Facilitative Transport Systemsmentioning
confidence: 99%
“…15) In addition to the shared mechanisms of transport of nucleobases and nucleosides, it has been suggested that there are independent transport processes specific for nucleosides or nucleobases. 16,17) Equilibrative nucleobase transport has been observed in human erythrocytes, human T-lymphoblastoid cells, LLC-PK1 cells, rabbit cornea cells and S49 mouse-derived lymphoma cells, [18][19][20][21] whereas concentrative nucleobase transport occurs in kidney, intestine, placenta, and choroid plexus. 19,[22][23][24][25][26] However, little is yet known about the molecular basis of nucleobase transport in mammalian cells.…”
mentioning
confidence: 99%
“…The almost 100-fold difference in K m for these transporters allows the study of the H2 transporter separately at a very low [ 3 H]hypoxanthine concentration. We have now determined the substrate recognition motif for H2 and compared it with that of the human facilitative diffusion nucleobase transporter (hFNT1), 1 which is the only nucleobase transporter in erythrocytes (11,12) but has also been described in various other tissues (13)(14)(15)(16)(17) and been shown to mediate the uptake of several chemotherapeutic purine analogues (17)(18)(19)(20). This approach to comparing transporters is all the more relevant because molecular approaches are unavailable: no protozoan or metazoan nucleobase transporters have yet been cloned.…”
mentioning
confidence: 99%